REVOLUTIONIZING HIGHER EDUCATION: THE TRANSFORMATIVE IMPACT OF ARTIFICIAL INTELLIGENCE ON TEACHING, LEARNING, AND CAREER PREPARATION - Farooq, Umaya; Malik, Sajad Ahmad; Syed, Altaf Shah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence (AI) is revolutionizing higher education, reshaping teaching methodologies, assessment practices, and career preparation. This paper explores AI’s transformative role, focusing on its ability to personalize learning, automate administrative tasks, and enhance the efficiency and fairness of assessments. AI-driven systems such as adaptive learning platforms and automated grading tools enable personalized education tailored to individual needs while providing timely feedback to students and easing educators’ workloads. Additionally, AI is influencing the job market by creating demand for advanced technical skills like data science and machine learning, alongside essential human-centric abilities like creativity and emotional intelligence. However, the integration of AI in education also presents challenges. Ethical concerns such as data privacy, algorithmic bias, and the diminishing role of human judgment in critical educational processes require careful consideration. Cognitively, AI’s limitations in understanding context and providing empathy underscore the need for a balanced approach where AI complements human insights rather than replaces them. To address these challenges, this paper recommends investing in teacher training, prioritizing ethical AI use, fostering skill development for an AI-driven workforce, and ensuring equitable access to AI technologies. The findings highlight the need for proactive strategies in higher education to harness AI’s potential while maintaining its human-centered focus. By aligning AI’s capabilities with educational goals, institutions can prepare students to thrive in an evolving global workforce while addressing ethical and cognitive implications.